NCF2 facilitates M2 macrophage polarization in glioblastoma through activation of the notch1–osteopontin axis - Zhang, Yinsong; Li, Na; Cheng, Hongbo; Xiang, Yi; Sun, Guozhu (Frontiers in Immunology, 2026)
BackgroundGlioblastoma (GBM), the most aggressive form of primary malignant brain neoplasm, is characterized by extensive invasiveness, high recurrence rates, and poor clinical outcomes. Tumor-associated macrophages, particularly those exhibiting an alternatively activated (M2) phenotype, play a critical role in promoting progression within the GBM environment. However, the molecular mechanisms underlying macrophage polarization in GBM remain insufficiently defined.MethodsThe expression of neutrophil cytosolic factor 2 (NCF2) was evaluated in GBM tissue specimens and cell lines using immunohistochemistry, western blot analysis, and reverse transcription polymerase chain reaction. Associations between NCF2, the M2 macrophage marker CD163, and osteopontin (OPN) were analyzed in 18 GBM specimens. Functional studies were performed by co-culturing human monocyte-derived macrophages with GBM cells that either overexpressed or exhibited silenced NCF2 expression. The roles of Notch1 signaling and OPN in NCF2-mediated macrophage polarization were evaluated using pharmacological inhibitors and neutralizing antibodies.ResultsNCF2 expression was significantly elevated in GBM tissues and cell lines and demonstrated a positive correlation with CD163+ M2 macrophage infiltration (r = 0.765, p < 0.001). In vitro assays indicated that NCF2 promoted polarization toward the M2 phenotype, as indicated by upregulation of CD163 and CCL18, without affecting proinflammatory markers such as TNF-α or CD86. NCF2 levels correlated positively with OPN expression (r = 0.745, p < 0.001), and OPN was identified as a downstream target regulated through the Notch1 pathway. Activation of Notch1 restored OPN expression in NCF2-silenced cells, whereas its inhibition reduced OPN expression in NCF2-overexpressing cells. Neutralization of OPN reversed the M2-polarizing effect induced by NCF2.ConclusionNCF2 contributes to the establishment of an immunosuppressive tumor microenvironment in GBM by promoting macrophage polarization via the Notch1–OPN pathway. These findings highlight NCF2 as a potential molecular target for therapeutic intervention in GBM.